VD_FINDINFO Jug / 2025 / 295 vom 30. Oktober 2024 - VD Tribunal cantonal (2024)
VIOLATION DU DEVOIR D'ASSISTANCE OU D'ÉDUCATION, LÉSION CORPORELLE SIMPLE, PEINE PÉCUNIAIRE | 123 ch. 2 al. 2 CP, 219 al. 1 CP